Kewenangan Badan Perencanaan Pembangunan Kota (BAPPEKO) Malang dalam Perencanaan, Kordinasi, dan Pengendalian Tata Ruang Kota - Syahrul Ibad (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
This research is motivated by the existence of social problems related to urban spatial planning faced by the people of Malang City, such as: increasing population, increasingly rapid development, traffic jams in certain areas, the air temperature is getting hotter. For this reason, it is necessary to plan and control a good urban spatial plan in order to create conditions for a directed and orderly arrangement of buildings in Malang City. The research results show that: 1). Bappeko authority: a). Authority in the preparation is carried out through six stages so that wisdom can regulate and achieve spatial goals that are comfortable, harmonious, and evenly distributed. b). The coordination authority carried out by Bappeko is still limited to the activities of agencies, agencies and districts by trying to organize and foster cooperation and synchronize all activities. c). The authority to control Bappeko starts from monitoring, reporting, evaluating to the means of control, namely policing, but the evaluation which is carried out every five years seems to legalize the violations that have occurred. 2). Bappeko's authority constraints in planning, coordination and control include: a). Internal; The lack of human resource capacity in the field of coordination and monitoring is due to the fact that the Bappeko structure does not have control sub-sectors. b). external; there is no technical clarity and guiding standards in control and there are local government interests for increasing local revenue (PAD) and the community's economy so that control is weak due to strong adherence to structural lines.